2010
DOI: 10.1111/j.1750-3841.2009.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Orange Juice of Batch Pasteurization in an Improved Pilot‐Scale Microwave Oven

Abstract: The effects on orange juice batch pasteurization in an improved pilot-scale microwave (MW) oven was evaluated by monitoring pectin methyl-esterase (PME) activity, color, carotenoid compounds and vitamin C content. Trials were performed on stirred orange juice heated at different temperatures (60, 70, 75, and 85 degrees C) during batch process. MW pilot plant allowed real-time temperature control of samples using proportional integrative derivative (PID) techniques based on the infrared thermography temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 20 publications
4
32
0
10
Order By: Relevance
“…The decrease in ascorbic acid (vitamin C) may be because of due to degradation of vitamin C because is heat labile nutrient. Our finding favors the findings of Cinquanta et al [20] who also reported the decrease in ascorbic acid (Vitamin C) during microwave pasteurization of orange juice. Figure 7 shows the effect of conventional and microwave heating pasteurization on Ascorbic Acid (Vitamin C).…”
Section: Effect Of Conventional and Microwave Heating Pasteurization supporting
confidence: 90%
“…The decrease in ascorbic acid (vitamin C) may be because of due to degradation of vitamin C because is heat labile nutrient. Our finding favors the findings of Cinquanta et al [20] who also reported the decrease in ascorbic acid (Vitamin C) during microwave pasteurization of orange juice. Figure 7 shows the effect of conventional and microwave heating pasteurization on Ascorbic Acid (Vitamin C).…”
Section: Effect Of Conventional and Microwave Heating Pasteurization supporting
confidence: 90%
“…The reduction in acidity during ripening plays an important role in the Brix: Acid ratio and consequently in influencing the taste and flavour of the juice (Braddock and Marcy, 1985;Akpapunam et al, 1993;Cinquanta et al, 2010;Ndife et al, 2013;Dauda and Adegoke, 2014). The increased soluble solids contents obtained compares with the result of Braddock and Marcy (1985).…”
Section: Physico-chemical Analysesmentioning
confidence: 97%
“…Nikdel et al (1993) and Cinquanta et al (2010) reported that continuous MWP of orange juice resulted in a reduction of PME residual activity of 0.5-1.5% at temperatures higher than 75 °C for 10-15 s and 2.5% at 70 °C for 1 min. Our results demonstrated that MW technology is suitable for decreasing enzyme activity using a short processing time, which would indicate that product stability could be preserved effectively.…”
Section: Enzyme Activitymentioning
confidence: 99%